2019
DOI: 10.47176/mjiri.33.129
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement in hospitals' surgery-related processes: A systematic review

Abstract: There is a growing global movement toward quality and safety in healthcare and quality improvement (QI) in general surgery. The identification of theoretical frameworks is the cornerstone of any QI program. →What this article adds: This is the first systematic review that aims to identify and evaluate QI models in surgery and provide an overview in this area. The results of this study can be used by health managers, researchers, and all those who are interested in quality improvement in hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
6
0
2
Order By: Relevance
“…We found few studies using QI methods,86–88 and few studies used implementation science methods10 12 17 89 which is of concern, as benefits of using these methods to support the delivery of evidence-based QI practices into routine healthcare, have been clearly demonstrated as critical to close the implementation gap. Indeed, there is wide acceptance that there is an implementation gap10 90 in scale up of evidenced based interventions into routine care in LMICs in general, and in surgical and anaesthesia care in particular 10 17 89 90.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found few studies using QI methods,86–88 and few studies used implementation science methods10 12 17 89 which is of concern, as benefits of using these methods to support the delivery of evidence-based QI practices into routine healthcare, have been clearly demonstrated as critical to close the implementation gap. Indeed, there is wide acceptance that there is an implementation gap10 90 in scale up of evidenced based interventions into routine care in LMICs in general, and in surgical and anaesthesia care in particular 10 17 89 90.…”
Section: Discussionmentioning
confidence: 99%
“…We found few studies using QI methods,86–88 and few studies used implementation science methods10 12 17 89 which is of concern, as benefits of using these methods to support the delivery of evidence-based QI practices into routine healthcare, have been clearly demonstrated as critical to close the implementation gap. Indeed, there is wide acceptance that there is an implementation gap10 90 in scale up of evidenced based interventions into routine care in LMICs in general, and in surgical and anaesthesia care in particular 10 17 89 90. Over the last two decades there have been seminal publications on implementation science including the Consolidated Framework for Implementation Research, which was originally published in 2009,91 Proctor’s Implementation Outcomes in 201120 and the Expert Recommendations of Implementing Change in 2015 19.…”
Section: Discussionmentioning
confidence: 99%
“…7 PDSA can be used in various surgical context and objectives such as to improve the quality of postoperative procedures, process mapping and finding improvable points in surgery, to improve communication between patient and medical staff, and to reduce patient waiting time before surgery. 8 Preoperative waiting time was lowered from 0.46 days to 0.29 days in 2008 following the implementation of a surgery admission unit for patients undergoing major elective surgery in Spain. 9 A study conducted at a university hospital in the Netherlands showed, initiation of an outpatient preoperative evaluation reduces preoperative admission time by a factor of 0.89 (95% CI, 0.88-0.91), rate of same-day admissions increased from 5.26% (692/13,162) to 7.72% (542/7024), and cancellation rate for medical reasons only reduced from 1.95% to 0.93%.…”
Section: Introductionmentioning
confidence: 99%
“…As surgery is one of the most resource-intensive areas of clinical medicine, there is a growing trend for quality improvement initiatives to improve the efficiency, quality, and safety of surgical care, to reduce unnecessary consumption of resources, and to increase patient satisfaction [ 6 ]. Some commonly used indicators to measure surgical care resource utilization include hospital length of stay (LOS), reoperation, and readmission.…”
mentioning
confidence: 99%